SUGGESTIONS FOR IMPROVEMENTS TO SPORE - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Miss Indranee Buldawoo, Rose Hill, Mauritius: 'I want to get acquainted with new techniques specially related to vegetable crops, seed technology, variety testing and various seed tests. I also wanted more information on hydroponics especially...